Consistency of In Vitro Chemoresponse Assay Results and Population Clinical Response Rates Among Women With Endometrial Carcinoma. Issue 3 (1st April 2011) - Huh, Warner K.; Cibull, Michael; Gallion, Holly H.; Gan, Christine M.; Richard, Scott; Cohn, David E.
Abstract : Background: There are a number of equally efficacious chemotherapy options for the treatment of women with endometrial cancer, all of which work in only a subset of those women with this disease. An in vitro assay performed before therapy initiation to identify the drug(s) most likely to be effective for the individual patient would have clinical utility. Such an assay should yield response rates similar to those found in treated patient populations. The purpose of this investigation was to determine whether the patterns of in vitro tumor response rates as determined by ChemoFx are consistent with expected population response rates. Methods: Nine hundred twenty-three tumor specimens from patients with high-risk early-stage, advanced stage, or recurrent endometrial cancer were sent for testing with the ChemoFx drug response marker from August 2, 2006, to August 31, 2009. Tumors were categorized as responsive (R), intermediately responsive (IR), or nonresponsive to each drug or combination tested. Response rates from clinical trials were identified and compared with the corresponding in vitro response rates. Results: Of the 923 specimens received, 759 (82%) were successfully tested by ChemoFx. Of these, 755 were tested for at least 1 of 5 National Comprehensive Cancer Network-recommended endometrial cancer drugs. The response rates (R+IR) for these drugs were as follows: 66% carboplatin-paclitaxel, 48% carboplatin, 37% cisplatin, 23% doxorubicin, and 36% paclitaxel. Moreover, 20% of tumors were pan-sensitive (R or IR) to all 5 regimens tested, 27% were pan-resistant (nonresponsive), and 53% showed different degrees of response to different drugs. Conclusions: ChemoFx in vitro response rates were consistent with published population response rates, and the ChemoFx drug response marker may provide clinically useful information to better optimize individual chemotherapy for treatment of women with endometrial cancer.